Valproic Acid Prodrug Affects Selective Markers, Augments Doxorubicin Anticancer Activity and Attenuates Its Toxicity in a Murine Model of Aggressive Breast Cancer - Nataly Tarasenko; Harel Josef Wilner; Abraham Nudelman; Gania Kessler-Icekson; Ada Rephaeli (MDPI AG, 2021)
We studied the unique inhibitor of the histone deacetylases (HDAC) valproate-valpromide of acyclovir (AN446) that upon metabolic degradation release the HDAC inhibitor (HDACI) valproic acid (VPA). Among the HDAC inhibitors that we have tested, only AN446, and to a lesser extent VPA, synergized with doxorubicin (Dox) anti-cancer activity. Romidepsin (Rom) was additive and the other HDACIs tested were antagonistic. These findings led us to test and compare the anticancer activities of AN446, VPA, and Rom with and without Dox in the 4T1 triple-negative breast cancer murine model. A dose of 4 mg/kg once a week of Dox had no significant effect on tumor growth. Rom was toxic, and when added to Dox the toxicity intensified. AN446, AN446 + Dox, and VPA + Dox suppressed tumor growth. AN446 and AN446 + Dox were the best inhibitory treatments for tumor fibrosis, which promotes tumor growth and metastasis. Dox increased fibrosis in the heart and kidneys, disrupting their function. AN446 most effectively suppressed Dox-induced fibrosis in these organs and protected their function. AN446 and AN446 + Dox treatments were the most effective inhibitors of metastasis to the lungs, as measured by the gap area. Genes that control and regulate tumor growth, DNA damage and repair, reactive oxygen production, and generation of inflammation were examined as potential therapeutic targets. AN446 affected their expression in a tissue-dependent manner, resulting in augmenting the anticancer effect of Dox while reducing its toxicity. The specific therapeutic targets that emerged from this study are discussed.